Review on Physicochemical Modification of Biodegradable Plastic: Focus on Agar and Polyvinyl Alcohol (PVA) - Mezigebu Belay (Advances in Materials Science and Engineering)
Plastics materials which are used in our daily life especially for packaging applications are derived from petrochemicals. Though these plastic materials satisfy the required properties of packaging materials in terms of strength, water resistance, and durability, they are not biodegradable and stay in landfills for plenty of years. This causes serious environmental threat and pollution. Owing to this, biodegradable plastics have been emerged as an alternative to conventional plastics. However, most of the biodegrade plastics are dependent on forest reserves even some may affect food supply. Nevertheless, agar and polyvinyl alcohol (PVA) neither causes deforestation nor affect the food stock. Though agar and PVA neither causes deforestation nor affect the food supply, they have high water absorption and a moderate tensile strength. This restricts the use of these polymers for applications. Researchers have used physicochemical modification methods to improve the properties of biodegradable polymers with due attention of agar and PVA. This review presents the basics of polymers, biodegradable polymers, chemistry of biodegradation, environmental impacts of biodegradable polymers, and the physicochemical modification of biodegradable polymers with a special focus of agar and PVA.